Inclusion of relational and cognitive dimensions in the assessment of older adult's mental competence in financial decision making - Orquiza, Mary Grace S. (Animo Repository, 2016)
Introduction: Financial decision making (FDM) is important in the autonomy and independence of older adults. Diseases causing cognitive impairments are common in older adults which compromise their FDM abilities. Clinical assessment is done to ensure FDM competence and protection from harm. Majority of FDM instruments measure behavioral outcomes and neglect cognitive aspect (how people think about decisions). Inclusionary approach in FDM is important to accommodate non-medical, inter-relational dimensions meaningful to decision makers. Objective: This study the cognitive aspect of financial decision making in the context of inter-relatedness, autonomy and independence, metacognition and cognitive impairment in the Filipino older adults. Methodology: Three studies were conducted. In Study 1, 20 older adults were interviewed about their narrative experience of FDM. Narratives were coded and analyzed thematically. In Study 2, FDM test (case scenarious, questions, scoring system) is developed based on narrative themes from study 1 and clinical standards. Ecological validity was established through an expert committee and pre-testing. Clinical testing was done to 116 older adults to determine group inclusion. FDM test was administered to 53 controls, 42 aMCI, and 21 Mild AD, quantitatively scored and statistically analyzed. Results: Study 1 showed significant strong repetitive themes on inter-relatedness, autonomy and independence, reflected in metacognition used in FDM. Study 2 showed differences in FDM scores among groups. Impoverished metacognitive knowledge of FDM was found in increasing severity of cognitive impairment.Conclusion: Dimensions of metacognition, inter-relatedness, autonomy and independence, and cognitive impairment contribute to variations in FDM. Development of detailed assessment and intervention taking into account these 4 dimensions will improve well-being and long-term planning in economic and health care for older adults and their family.